Infant Brain Development in First 3 Months - J Gordon Millichap; John J Millichap (Pediatric Neurology Briefs Publishers, 2014)
Investigators at University of California, San Diego, and centers in Hawaii and Trondheim, Norway, examined structural growth trajectories and rates of change in the whole brain and regions of interest in infants during the first 3 months after birth.